Effects of coal pore structure on methane‐coal sorption hysteresis: An experimental investigation based on fractal analysis and hysteresis evaluation. (1st June 2020) - He, Xinxin; Cheng, Yuanping; Hu, Biao; Wang, Zhenyang; Wang, Chenghao; Yi, Minghao; Wang, Liang
Abstract: To investigate the effects of coal pore structure on the methane‐coal sorption hysteresis, six coal samples were collected. The methane‐coal sorption measurement was performed at 35 °C and pressure up to 5.5 MPa using a high-pressure volumetric analysis system (HPVAS). With the help of N2 physisorption at 77 K and CO2 physisorption at 273 K, basic pore properties including specific surface area (SSA), mode diameters and pore size distribution (PSD) were obtained through classical thermodynamic methods and the advanced density functional theory (DFT). A Fréchet distance index (FDI) based on the resemblance of two curves was proposed to overcome the difficulty in quantitatively evaluating the methane‐coal sorption hysteresis. Quantified heterogeneity of the coal pore structure by five fractal dimensions derived from Frenkel-Halsey-Hill model ( D FHH1 and D FHH2 ), Neimark-Kiselev model ( D NK ), Wang-Li model ( D WL ) and Sierpinski model ( D SPS ) was coupled with the FDI for regression analyses. Results indicate that increasing SSA and stronger first-layer adsorption energy may exacerbate the methane-coal sorption hysteresis, while no satisfactory correlation was observed between the methane-coal sorption hysteresis and the pore volume. Wider Dubinin-Astakhov PSD and bigger mode diameters were found corresponding to smaller FDIs indicating reduced methane-coal sorption hysteresis. Correlation between the FDI and the fractal dimensions revealed a possible positive correlation between the methane-coal sorption hysteresis and the heterogeneity of the coal pore structure, especially for D FHH2 whose applied pore widths were 2.78–385 nm.